(untitled) (Nordic Journal of Practical Theology, 2020)
Focal points of this article are preconditions and obstacles for the further establishing and increasing professionalisation of a specific field of pastoral care in the Lutheran Folk Church of Denmark (CoD). Since the mid-eighties general specialisation in society has implied a development of a multitude of chaplaincy in public domains in Denmark (Kühle & Christensen, 2019:182). This has generated an increase in numbers of chaplains in health care. In this paper we aim to show main trends in the development and current state of spiritual care1 and hospital chaplaincy in Denmark and include first results from a proscriptive audit pilot developed for internal quality assessment and development.2